A review on enhancing education with AI: exploring the potential of ChatGPT, Bard, and generative AI - Anduamlak Abebe Fenta (Discover Education)
Abstract Generative AI systems, such as ChatGPT and Bard, can significantly enhance education by providing personalized learning experiences. They can tailor content, quizzes, and explanations to individual students; act as virtual tutors, and offer instant feedback. However, privacy concerns have arisen because of the need for personal data. Ensuring ethical AI use, transparency, and student privacy is essential. Although AI can automate tasks and analyze student performance, there are concerns about job displacement and the devaluation of human teaching. The rapid advancement of AI has raised questions about the relevance of traditional curricula and the need for educators’ upskilling. Integrating AI into education requires careful consideration of ethical, privacy, and pedagogical factors to maximize benefits and mitigate challenges.